Electric field generation of Skyrmion-like structures in a nematic liquid crystal. Issue 3 (9th November 2015) - Cattaneo, Laura; Kos, Žiga; Savoini, Matteo; Kouwer, Paul; Rowan, Alan; Ravnik, Miha; Muševič, Igor; Rasing, Theo
Abstract : We report the generation of stable Skyrmion-like structures in a thin nematic liquid crystal film on chemically patterned patchy surfaces. Abstract : Skyrmions are particle-like topological objects that are increasingly drawing attention in condensed matter physics, where they are connected to inversion symmetry breaking and chirality. Here we report the generation of stable Skyrmion-like structures in a thin nematic liquid crystal film on chemically patterned patchy surfaces. Using the interplay of material elasticity and surface boundary conditions, we use a strong electric field to quench the nematic liquid crystal from a fully aligned phase to vortex-like nematic liquid crystal structures, centered on patterned patches, which carry two different sorts of topological defects. Numerical calculations reveal that these are Skyrmion-like structures, seeded from the surface boojum topological defects and swirling towards the second confining surface. These observations, supported by numerical methods, demonstrate the possibility to generate, manipulate and study Skyrmion-like objects in nematic liquid crystals on patterned surfaces.